Judeo-Arabic as a Frontier of Interaction between the Jews and Muslims - Leonard Chrysostomos Epafras (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2017)
As a continued discussion about the Judeo-Arabic as a cultural symbiosis of the Jews in the Islamicate context, the present article enhances it with the discussion of frontier as a theoretical framework to understand the Jewish condition in the Muslim realm, in particular in Al-Andalus. Hence, the Judeo- Arabic becomes an actualization of the politics of language by the Jews. In addition to the fact that the Judeo-Arabic being nurtured by the Arabic literature, the Jews also carried out their experiences in diaspora critically through the usage of the Arabic and the Judeo-Arabic cultural container.DOI: 10.15408/insaniyat.v1i2.5472